Evaluation of neoadjuvant immunotherapy plus chemotherapy in Chinese surgically resectable gastric cancer: a pilot study by meta-analysis - Xu, Hao; Li, Tengyun; Shao, Guoyi; Wang, Weizhi; He, Zhongyuan; Xu, Jianghao; Qian, Yawei; Liu, Hongda; Ge, Han; Wang, Linjun; Zhang, Diancai; Yang, Li; et al. (Frontiers in Immunology, 2023)
Background: Recently, the use of immunochemotherapy in the treatment of advanced gastric cancer (GC) has been increasing and programmed cell death protein 1 (PD-1) inhibitors combined with chemotherapy has become the first-line treatment for advanced GC. However, few studies with small sample sizes have examined this treatment regimen to assess its effectiveness and safety in the neoadjuvant treatment phase of resectable local advanced GC. Materials and Methods: Herein, we systematically searched PubMed, Cochrane CENTRAL, and Web of Science for clinical trials on neoadjuvant immunochemotherapy (nICT) in advanced GC. The primary outcomes were effectiveness [evaluated by major pathological response (MPR) and pathological complete response (pCR)] and safety [ assessed by grade 3–4 treatment-related adverse events (TRAEs) and postoperative complications]. A meta-analysis of non-comparative binary results was performed to aggregate the primary outcomes. Direct comparative analysis was used to compare pooled results of neoadjuvant chemotherapy (nCT) with nICT. The outcomes emerged as risk ratios (RR). Results: Five articles with 206 patients were included, and all of them were from the Chinese population . The pooled pCR and MPR rates were 26.5% (95% CI: 21.3%–33.3%) and 49.0% (95% CI: 42.3%–55.9%), while grade 3–4 TRAEs and post-operative complication rates were 20.0% (95% CI: 9.1%–39.8%) and 30.1% (95% CI: 23.1%–37.9%), respectively. Direct comparison showed that with the exception of grade 3–4 TRAEs and postoperative complications, all outcomes including pCR, MPR, and R0 resection rate favoured nICT to nCT. Conclusion: nICT is a promising strategy for use as an advisable neoadjuvant treatment for patients with advanced GC in Chinese population. However, more phase III randomized controlled trials (RCTs) will be required to further consolidate the efficacy and safety of this regimen.